2014
DOI: 10.7196/samj.8338
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in the developing world: Evaluating the iPhone mobile device as a screening tool

Abstract: Background. Developing countries have the world's highest prevalence of hearing loss, and hearing screening programmes are scarce. Mobile devices such as smartphones have potential for audiometric testing. Objectives. To evaluate the uHear app using an Apple iPhone as a possible hearing screening tool in the developing world, and to determine accuracy of certain hearing thresholds that could prove useful in early detection of hearing loss for high-risk populations in resource-poor communities.Methods. This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 20 publications
3
97
0
7
Order By: Relevance
“…The uHear, for example, is a smartphone-based application for Apple iOS and is a self-administered air conduction threshold test (Peer & Fagan, 2015). Studies conducted on this application have yielded mixed outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The uHear, for example, is a smartphone-based application for Apple iOS and is a self-administered air conduction threshold test (Peer & Fagan, 2015). Studies conducted on this application have yielded mixed outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted on this application have yielded mixed outcomes. In some studies, the uHear™ was said to accurately identify disabling hearing loss, detect early high frequency threshold changes (Peer & Fagan, 2015), rule out moderate hearing losses and determine the degree of hearing loss (Szudek, Ostevik, Dziegielewski, Robinson-Anagor, Gomaa, Hodgetts & Ho, 2012;Abu-Ghanem et al, 2015). However, in other studies, the uHear™ was found to produce elevated thresholds when compared to manual audiometry (Szudek et al, 2012;Khoza-Shangase & Kassner, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Smartphones have the potential to test hearing through audiometric applications. Given the upsurge of mobile technology in Africa, Peer and Fagan [5,6] evaluated the uHear app (using an Apple iPhone) as a possible hearing screening tool in the developing world. They conclude that it is a feasible screening test to rule out significant hearing loss (pure-tone average >40 dB).…”
Section: Testing Hearing With Smartphonesmentioning
confidence: 99%